EXPERIMENTAL ANALYSIS OF THERMAL STRATIFICATION IN SHALLOW SOLAR PONDS UNDER NATURAL SUNLIGHT - Morka, John C.; Eseka, K.; Ilugo, N. T.; Kanayo, Samuel; Jackson-Abara, M. E. (FUDMA JOURNAL OF SCIENCES, 2025)
The core research objectives is to investigate and analyze the phenomenon of thermal stratification in shallow solar ponds. The solar pond consists of the plastic bag and the encasement box; for the plastic bag, two transparent polythene materials of 75 cm x 55 cm were heat – seated with soldering bar at about 250OC. One side of the bag was pointed with bituminous black selection. A CDG-10B solar radiation sensor pyranometer and a thermograph were used to record the climatological data of solar irradiance and the ambient temperature respectively. A wooden box having three apartments was constructed. The lower convective zone, non- convective zone and the upper convective zone, each playing role in heat collection and storage.In the first mode of operation, the temperature indicated a maximum of 77OC at  1.30 pm.in the second mode of operation, the temperature indicated a maximum 85oC at 3.00pm. While in the third mode operation, the temperature indicated a maximum of 86OC at about 3.00pm. By providing a low – cost sustainable solution for heating and electricity generation, enabling efficient thermal energy storage for application like water heating, space heating or agricultural drying, and by offering a potential alternative to fossil fuels, reducing energy costs and environmental impact, this study and its findings can contribute to solar energy utilization and thermal energy storage in low resource settings.
Keywords: Thermal Behaviour; Shallow; Solar Pond; Investigating